Effect of temperature, permanent type and bacterial degradation on the permeability of a proposed landfill liner from recycled laminated plastic materials - Bilaro, Virgil B.
Recycling is currently one of the viable options to deal with plastic wastes to lessen its impact on the environment. Commercial recycling operations focus mostly of plastics made of a single polymer type. Plastic laminates are difficult to recycle since they are usually made up of different polymer types. The study of Senoro shows (Senoro 2006) that laminated physical wastes can be recycled into sheet forms that possess sufficient physical, mechanical , and chemical properties to function as a landfill liner. Yet, it has to be proven if the recycled material could effectively contain landfill leachate and prevent the transport of contaminants through it. The Ecological Solid Waste Management Act of 2000 (RA 9003) defines a liner as "a system of clay layers and/or geosynthetic membranes used to contain leachate and reduce or prevent contaminant flow to groundwater". Impermeability is an essential characteristic of any liner material, since its very function is pollutant containment.